Crystal structures of (2,2′-bipyridyl-κ2N,N′)bis[N,N-bis(2-hydroxyethyl)dithiocarbamato-κ2S,S′]zinc dihydrate and (2,2′-bipyridyl-κ2N,N′)bis[N-(2-hydroxyethyl)-N-isopropyldithiocarbamato-κ2S,S′]zinc - Siti Artikah M. Safbri; Siti Nadiah Abdul Halim; Edward R. T. Tiekink (Acta Crystallographica Section E: Crystallographic Communications, 2016)
The common feature of the title compounds, [Zn(C5H10NO2S2)2(C10H8N2)]·2H2O, (I), and [Zn(C6H12NOS2)2(C10H8N2)], (II), is the location of the ZnII atoms on a twofold rotation axis. Further, each ZnII atom is chelated by two symmetry-equivalent and symmetrically coordinating dithiocarbamate ligands and a 2,2′-bipyridine ligand. The resulting N2S4 coordination geometry is based on a highly distorted octahedron in each case. In the molecular packing of (I), supramolecular ladders mediated by O—H...O hydrogen bonding are found whereby the uprights are defined by {...HO(water)...HO(hydroxy)...}n chains parallel to the a axis and with the rungs defined by `Zn[S2CN(CH2CH2)2]2'. The water molecules connect the ladders into a supramolecular layer parallel to the ab plane via water-O—H...S and pyridyl-C—H...O(water) interactions, with the connections between layers being of the type pyridyl-C—H...S. In (II), supramolecular layers parallel to the ab plane are sustained by hydroxy-O—H...S hydrogen bonds with connections between layers being of the type pyridyl-C—H...S.